Stakeholders and network analyses in Tambora National Park, Sumbawa Island, Indonesia - MUHAMMAD ANSHOR; SAMBAS BASUNI; HARNIOS ARIEF; TUTUT SUNARMINTO (Society for Indonesian Biodiversity, 2023)
Abstract. Anshor M, Basuni S, Arief H, Sunarminto T. 2023. Stakeholders and network analyses in Tambora National Park, Sumbawa Island, Indonesia. Biodiversitas 24: 5446-5463. The complexity of managing Tambora National Park (Tambora NP), West Nusa Tenggara Province, Indonesia poses a challenge to be overcome effectively by Tambora NP Office alone, thus the involvement of broader stakeholders is needed. These stakeholders have their respective levels of influence and interests which affect the relationship between them and Tambora NP Office. Therefore, this study aimed to identify the stakeholders related to the management of Tambora NP, and investigate their interests and influence using social network analysis. A stakeholder analysis was conducted by the following steps: (i) identifying the stakeholders, (ii) mapping the stakeholders, and (iii) assessing the relationship among stakeholders. The analysis identified 38 stakeholders related to Tambora NP management. Tambora NP Office is the primary stakeholder with the highest level of influence and interest. The relationship established in the management network of Tambora NP is still weak and centralized among several stakeholders in which Tambora NP Office is the most central stakeholder. The relationship among stakeholders is dominated by five stakeholders, namely Tambora NP Office, Natural Resources Conservation Agency of West Nusa Tenggara (BKSDA NTB), Executive Board (DP) of Geopark Tambora, Forest Management Unit (KPH) Tambora and the Environment and Forestry Provincial Service of West Nusa Tenggara Province (Dinas LHK NTB). These five institutions also dominate the proximity between stakeholders, so the information flow is not evenly distributed to all stakeholders. The weak relationships among stakeholders could be overcome by enhancing the flow of information and communication which could be facilitated by Tambora NP Office, BKSDA NTB, and DP Geopark Tambora.